SOME ASPECTS OF IMPROVING THE ACTIVITIES OF SPECIAL INSTITUTIONS OF THE PUBLIC ORDER SERVICE OF INTERNAL AFFAIRS BODIES - Khudayshukurov Farkhod Tursoatovich (American Journals, 2023)
The article describes the reforms carried out in the activities of special institutions of the public order service of the internal affairs bodies, in particular the legislative acts adopted in the field and the results obtained by their implementation in logical consistency, and provides feedback on the prospects for improving the legal provision of this direction.
Keywords: internal affairs Bodies, Public Order Maintenance, special Institutions, Reforms, legal basis.